External Adjustment and the Optimal Demand for International Reserves. (IMF Working Papers; Working Paper, 1989)
This paper provides a theoretical underpinning for the major determinants of optimal reserve demand in the case where fundamental disequilibrium constitutes a key element governing reserve management. Emphasis is given to the role of reserves to smooth the process of economic adjustment by financing part of external disequilibrium, as well as to meet temporary random fluctuations in the excess demand for foreign exchange. The analysis incorporates this financing aspect of reserve holdings into a simple inventory model and discusses the optimal stock of reserves in the context of the optimal mix of adjustment and financing.